A Minskyan criticism on the shareholder pressure approach of financialisation - Ilhan Dögüs (Universität Hamburg, Zentrum für Ökonomische und Soziologische Studien (ZÖSS), 2016)
In this paper, the Post-Kaleckian approach on financialisation which argues that investment of Nonfinancial Corporations in real capital assets has been restricted by the rising dividend and interest payments due to shareholder pressure will be criticized based on a Minskyan understanding of investment. It will be put forward that, reinvestment of profits in capital assets has decreased because of declined quasi-rent expectations induced by depressed demand.
Keywords: E12; E22; E44; 330; financialisation; shareholder pressure; Minsky; capital assets; financial assets